Contractors' perception towards behavior-based safety (BBS) system in construction industry / Nina Sakina Fourzan - Fourzan, Nina Sakina (2020)
Construction accidents among general workers are one of the critical sectors that the current safety practices should be upgraded. Mostly accidents are caused by unsafe behaviors, poor environment of the workplace or both. While there has been dramatic enhancement in making more secure construction environment, the construction accident still tend to occur due to the construction workers unsafe act. The aim of this research is to study the contractor's perception on behaviour-based safety (BBS] system in construction industry. There are three main objectives for this study which are to explore issue on site management and identify the term of behaviour-based safety (BBS) system.